CAR RENTAL COMPENSATION PERSPECTIVE MUI FATWA NUMBER 43/DSN-MUI/VIII/2004 (CASE STUDY OF NADIA RENT CAR MEDAN) - Putra Daulay, Daulat Baginda; Lubis, Fauziah (Academy of Education Journal, 2023)
The purpose of this research is to find out the steps for settlement of compensation in the practice of renting a car based on the perspective of the MUI Fatwa Number 43/DSN-MUI/VIII/2004. The formulation of the problem used is how to settle compensation for parties who default (consumers) on verbal agreements made by rental owners (manufacturers) based on MUI Fatwa Number 43/DSN-MUI/VIII/2004. This research includes qualitative research using juridical research methods that use two sources, namely primary and secondary. As well as conducting interviews with several car rental users in Medan City, Medan Marelan District. The results of this study show that several car rental users make verbal agreements between consumers and producers. Regardless of the consequences of the agreement made verbally which will be accepted if one of the agreements is forgotten or not pronounced at the time of the contract, then it will be detrimental to one of the parties. If the consumer commits a default that does not comply with the verbal agreement at the outset, then the consumer will compensate for the loss determined by the producer. According to the perspective of the MUI Fatwa Number 43/DSN-MUI/VIII/2004 general provision number 4, namely the amount of compensation (ta'widh) is in accordance with the value of real compensation (real loss) that must be experienced (fixed cost) in the transaction and not a loss expected to occur (potential loss) due to missed opportunities (opportunity loss or al-furshah al-dhai'ah). Where is the compensation that must be completed according to the agreement made at the beginning by the producer at the beginning, even if it was done verbally